Development of linux device driver for programmable peripheral interface - 391572 Sazrul Azri Zakariya (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2000